2000
DOI: 10.1037/0022-3514.78.6.1092
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cognitive load on self-presentation: Can cognitive busyness help as well as harm social performance?

Abstract: Extra cognitive loads can hinder challenging self-presentations by usurping needed cognitive resources but also may sometimes improve them by shifting attention away from negative self-preoccupation. In Study 1, extraverts and introverts participated in an interview in which they presented themselves as either extraverted or introverted. Congruent self-presentations, which should be cognitively nondemanding, were unaffected by a cognitive busyness manipulation (rehearsing an 8-digit number). However, incongrue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Participants who used nondefault self-presentational strategies (e.g., modesty with strangers) were not able to pursue these strategies automatically and used conscious cognitive resources to accomplish their goals (see also Patterson, Churchill, Farag, & Borden, 1991/1992. Other research has also demonstrated that self-presenting in a way that is inconsistent with personality is cognitively taxing and requires attentional resources (Pontari & Schlenker, 2000).…”
Section: Impression Management and Personality Expressionmentioning
confidence: 99%
“…Participants who used nondefault self-presentational strategies (e.g., modesty with strangers) were not able to pursue these strategies automatically and used conscious cognitive resources to accomplish their goals (see also Patterson, Churchill, Farag, & Borden, 1991/1992. Other research has also demonstrated that self-presenting in a way that is inconsistent with personality is cognitively taxing and requires attentional resources (Pontari & Schlenker, 2000).…”
Section: Impression Management and Personality Expressionmentioning
confidence: 99%
“…For example, Pontari and Schlenker (2000) assessed accuracy of recall in a role-playing task only for people scoring in the outer tertiles of an introversion/extraversion scale. Similarly, Deffenbacher, Huff, Lynch, Oetting, and Salvatore (2000) administered the Driving Anger Scale to a large sample as a screening instrument, retaining for further analysis only those individuals scoring in the upper and lower quartiles.…”
mentioning
confidence: 99%
“…Similarly, placing participants under a large memory load restricts people's capacity to think carefully and deliberatively (e.g., Gilbert & Osborne, 1989;Krull, Seger, & Silvera, 2008;Pontari & Schlenker, 2000). For example, Pontari and Schlenker (2000) demonstrated that when people are under memory load (i.e., rehearsing an 8-digit number while performing a concurrent task), they are less efficient at the demanding task of presenting themselves as an introvert when they are actually an extrovert. Finally, the REI has been shown to predict differences in behavior and cognition in regards to experiential and rational thinking styles (e.g., Pacini & Epstein, 1999).…”
Section: How Much Does Effortful Thinking Underlie Observers' Reactiomentioning
confidence: 99%
“…Manipulating the time available for participants to make their responses is a well-documented way to produce cognitive load, as little time is available for people to think rationally, make complex links, or fully utilize controlled cognitive resources (e.g., Hernandez & Preston, 2013;Rand et al, 2012). Similarly, placing participants under a large memory load restricts people's capacity to think carefully and deliberatively (e.g., Gilbert & Osborne, 1989;Krull, Seger, & Silvera, 2008;Pontari & Schlenker, 2000). For example, Pontari and Schlenker (2000) demonstrated that when people are under memory load (i.e., rehearsing an 8-digit number while performing a concurrent task), they are less efficient at the demanding task of presenting themselves as an introvert when they are actually an extrovert.…”
Section: How Much Does Effortful Thinking Underlie Observers' Reactiomentioning
confidence: 99%
See 1 more Smart Citation